Anita gets bail: what are our courts doing? What should we do about them? - Shourie, Arun (HarperCollins Publishers India, 2018)
For a house we never built on a plot we did not own -- Justice done, undone, redone -- Prosecutor hunting, and other devices -- When courts are compelled to step out of their domain -- Adherence? -- When one of our own is invovled -- Bane hain ahl-e-havas muddai bhi munsif bhi ... -- What if he had not written that letter? -- Eloquence -- And yet I am taken by surprise -- So much science -- Thinking through -- Circumstances, consequences, meta-consequences